ANALISIS ASPEK FUNDAMENTAL DAN PSIKOLOGIS TERHADAP PERUBAHAN KURS VALAS DI INDONESIA PERIODE 2004 – 2012 - Ria Safitri '; Ria Nelly Sari; Gusnardi ' ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
Exchange rate stability is one important factor in keeping the economy, because the exchange rate is a representation of the international financial and economic conditions. For the stability of the exchange rate must be obtained, maintained and attempted to obtain a stronger exchange rate to shocks. Especially since the introduction of free-floating exchange rate system in Indonesia, where the determination of the Indonesia exchange rate against foreign currencies left entirely to the market mechanism that giving more opportunities for market participant to speculate that impact in fluctuating exchange rate prediction becomes difficult to predict. The main problem in this research is how the fundamental factors which consists of inflation (INF), interest rate (SBI), GDP, money supply (JUB), current account (CA), the capital account (CFA), external debt and speculation that psychological factors and interventions affect the exchange rate changes. While the purpose of this study is to get empirical evidence of fundamental and psychological factors influence the rate changes. The data used in the form of secondary data obtained from several central banks. Data collected from the period 2004 Q1 to 2012 Q4. Based on purposive sampling technique, chosen to be analyzed is 3 rate, USD / GBP, JPY / USD and AUD / USD. In this study, data analysis was conducted using OLS and variance ARCH GARCH models Based on the research results, it was concluded all of the variables used in this study affect in three exchange rate sample that was studied, except for a variable money supply that does not affect the exchange rate of JPY / USD. It can be caused by actors who tend to pay attention to forex technical analysis and forex psychological. Based on the technical analysis of the movement of JPY / USD exchange rate movements rely heavily on USD / IDR, in addition to the fundamentals of money supply by simply giving effect indirectly through inflation and interest rates. The total effect of all variables on each exchange rate amounted to 47%, 41% and 43% while about 66% are caused by other variables outside of this study.Kata Kunci : Exchange rate, inflation, SI, GDP, JUB, ED, CA, C